Acute Coinfection with Hepatitis B and Hepatitis C Viruses - Brian M Yan; Samuel S Lee (Canadian Journal of Gastroenterology)
Acute coinfection of hepatitis B virus (HBV) and hepatitis C virus (HCV) is rare. The few previously reported cases all describe acute HBV followed by acute HCV, leading to HBV clearance but chronic HCV. This is the first reported case of acute concurrent infection and spontaneous clearance of both HBV and HCV.